Optimization of Online Learning During the Covid-19 Pandemic in Rural Areas - Rica Marhayati; Rahma Diani; Antomi Saregar; Dwi Fujiani; Fredi Ganda Putra; Megawati Ridwan Fitri (Smart Society, 2022)
The Covid-19 pandemic has forced us to carry out all activities, including teaching and learning. The appropriate learning model in this situation is the distance learning model. However, the distance learning model is a new learning model that needs to be socialized and reminded to teachers and student guardians. This community service research aims to conduct distance learning training for teachers and student guardians in Gudung Negara village. The method used was door-to-door socialization to avoid crowds and prevent the spread of Covid-19. Teachers and guardians understood to do activities indirectly and adapted to carrying out learning during the Covid-19 pandemic. This community service activity resulted in student guardians supporting schools in conducting learning activities during the Covid-19 pandemic. Furthermore, teachers could design lesson plans, and student guardians could use the Google Meet platform. Based on this community service activity, as a follow-up, it is hoped that policymakers and relevant institutions will take part in mentoring and supporting teachers in managing learning as well as monitoring and evaluating the learning process during the COVID-19 pandemic